Comparison of scenarios in the trajectory of body mass index among adolescents monitored in primary health care: the VigiNUTRI Brazil study - Rafaella Lemos Alves; Natacha Toral; Vitor Paravidino; Vivian S. S. Gonçalves (Scientific Reports)
Abstract We compared the BMI-for-age (BMI/A) trajectory of Brazilian adolescents monitored in the primary health care (PHC) setting based on a simulated scenario. We used a real-life cohort of adolescents monitored by the Food and Nutrition Surveillance System (Sisvan) between 2008 and 2018. The LMS method was employed to estimate the simulated BMI/A evolution curve, assuming that the adolescents maintained the conditions observed during their first assessment (simulation curve). This curve was compared with that of the real-world cohort (Sisvan curve). Both curves were compared to the World Health Organization (WHO) reference cutoff. The difference in the BMI/A trajectory between the two curves was evaluated using linear mixed-effects models. When the participants started adolescence, their BMI/A was above the reference range. The Sisvan curve revealed that girls had a BMI/A that was higher than the simulated value at age 19 (p < 0.001) and that exceeded the WHO reference cutoff value; this finding was particularly pronounced in the southern region (Sisvan: 23.89 kg/m2; simulation: 23.57 kg/m2; WHO: 21.4 kg/m2). The BMI of boys decreased after age 13 (p < 0.001) but remained higher than the reference value. Monitoring nutritional status in the PHC setting may have been more effective at controlling excess weight in boys, emphasizing the importance of improving care.